2013
DOI: 10.1192/bjp.bp.112.116178
|View full text |Cite
|
Sign up to set email alerts
|

Common mental disorders, neighbourhood income inequality and income deprivation: small-area multilevel analysis

Abstract: Background Common mental disorders are more prevalent in areas of high neighbourhood socioeconomic deprivation but whether the prevalence varies with neighbourhood income inequality is not known. Aims To investigate the hypothesis that the interaction between small-area income deprivation and income inequality was associated with individual mental health. Method Multilevel analysis of population data from the Welsh Health Survey, 2003/04–2010. A total of 88 623 respondents aged 18–74 years were nested within 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
56
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 30 publications
6
56
2
Order By: Relevance
“…These studies assessed depression 28,37,41,51 , psychological distress/symptoms 31 and psychosis 26,27,32,45 . Ten articles reported mixed results: four of them found that greater income inequality was associated with higher prevalence/incidence of mental health problems in some population subgroups 29,30,36,40 , such as females 30 or low-income groups 36 or countries with high HDI 29 ; one article 47 reported that income inequality was associated with depression, but not with anxiety or any mental disorders; one article 44 reported that greater income inequality was associated with lower prevalence of common mental disorders at community level, and higher prevalence at region level; one article 12 found association at country level, and only among women and children at state level; in one article 46 greater income inequality was associated with higher prevalence of common mental disorders in high-income areas, and with lower prevalence in low-income areas. Eight articles 34,38,39,42,43,[49][50][51] found nonsignificant associations.…”
Section: Table 1 About Herementioning
confidence: 99%
See 3 more Smart Citations
“…These studies assessed depression 28,37,41,51 , psychological distress/symptoms 31 and psychosis 26,27,32,45 . Ten articles reported mixed results: four of them found that greater income inequality was associated with higher prevalence/incidence of mental health problems in some population subgroups 29,30,36,40 , such as females 30 or low-income groups 36 or countries with high HDI 29 ; one article 47 reported that income inequality was associated with depression, but not with anxiety or any mental disorders; one article 44 reported that greater income inequality was associated with lower prevalence of common mental disorders at community level, and higher prevalence at region level; one article 12 found association at country level, and only among women and children at state level; in one article 46 greater income inequality was associated with higher prevalence of common mental disorders in high-income areas, and with lower prevalence in low-income areas. Eight articles 34,38,39,42,43,[49][50][51] found nonsignificant associations.…”
Section: Table 1 About Herementioning
confidence: 99%
“…Eight articles reported results from multi-country studies 12,27,29,[31][32][33][34][35] ; ten studies were conducted in the USA 28,30,[36][37][38][39][40][41][42][43] ; three studies were carried out in the UK [44][45][46] ; two articles reported results from a study carried out in Brazil 47,48 ; one study was conducted in Australia 49 , one in Mexico 50 , one in Spain 51 , and one in South Africa 26 (Table 1).…”
Section: Figure 1 About Herementioning
confidence: 99%
See 2 more Smart Citations
“…(3) And among mental disorders, this study analyzed common mental disorder (CMD), as it represents the most prevalent disorder in the world population. (2,4) The common mental disorder, also called non-psychotic mental disorder, is diagnosed when people are mentally ill and present somatic symptoms such as irritation, fatigue, forgetfulness, concentration decrease, anxiety and depression. (2,5) Global projections for 2030 seek to include these disturbances among the most disabling for human beings.…”
Section: Introductionmentioning
confidence: 99%